2007
DOI: 10.14310/horm.2002.111108
|View full text |Cite
|
Sign up to set email alerts
|

Coronary calcification in patients with end-stage renal disease: a novel endocrine disorder?

Abstract: cardiovascular mortality is significantly increased among patients with end-stage renal disease. the commonly observed vascular calcification in such patients has been considered as one of the causative factors. In patients undergoing dialysis, the incidence of coronary artery calcification is 2-5 times higher compared to patients with normal renal function and angiographically demonstrated coronary artery disease. Moreover, epidemiological studies have revealed a significant correlation of the extent of coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Cardiovascular diseases account for 50% of mortality in patients with end-stage kidney disease (ESKD) [1]. The prevalence of these diseases among hemodialysis patients is about 10-30 times higher than that among general population of the same age and sex [2]. The high prevalence of cardiovascular events in ESKD patients is associated with traditional risk factors including hypertension, dyslipidemia, diabetes mellitus, and smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases account for 50% of mortality in patients with end-stage kidney disease (ESKD) [1]. The prevalence of these diseases among hemodialysis patients is about 10-30 times higher than that among general population of the same age and sex [2]. The high prevalence of cardiovascular events in ESKD patients is associated with traditional risk factors including hypertension, dyslipidemia, diabetes mellitus, and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular and valvular calci ications are the most common forms of extra-osseous calci ication in ESKD patients [2]. CVC is associated not only with the traditional risk factors, but also with factors such as abnormalities in the levels of calcium, phosphorus, PTH, and vitamin D [5].…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 54 ] MHD is the preferred treatment for patients with ESRD, but the degree of CAC in MHD patients is 2–5-fold higher than that of patients with angiographic evidence of coronary artery disease. [ 41 55 ] In one study, 79% of CRD patients had vascular calcification before they received MHD and, afterward, the proportion was close to 100%,[ 56 ] suggesting that, besides the factors mentioned above, other factors that affect calcification might be involved.…”
Section: O Ther F Actorsmentioning
confidence: 99%
“…With regard to diagnosis of CAC, spiral computer tomography evidenced the relationship between serum fetuin-A levels and degree of coronary calcifications [26]. Concerning this, Efstratiadis and coworkers demonstrated that electron beam computer tomography and multi-detector computer tomography represent the most commonly used non-invasive modalities for the assessment of coronary calcifications [27].…”
Section: Fetuin-a In Esrd Patientsmentioning
confidence: 99%